2010
DOI: 10.1542/peds.2008-3632
|View full text |Cite
|
Sign up to set email alerts
|

Bruising Characteristics Discriminating Physical Child Abuse From Accidental Trauma

Abstract: Discriminating differences exist in bruising characteristics for abusive versus accidental trauma. The body region- and age-based bruising clinical decision rule model functions as a clinically sensible screening tool to identify young children who require further evaluation for abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(170 citation statements)
references
References 27 publications
(29 reference statements)
5
150
1
5
Order By: Relevance
“…75 There is ample evidence that evaluating bruising patterns in abused and nonabused children helps to identify specific ages, locations, and patterns of bruising that are highly correlated with child abuse. [76][77][78][79][80][81] In children with bruising related to normal activity, the prevalence and mean number of bruises increases with age, and the majority of preschool-aged and schoolchildren have accidental bruises. 82 The commonest sites of bruising in nonabused, ambulatory children are to the knees and shins, and the vast majority of normal bruises are over bony prominences, including the forehead.…”
Section: Skin Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…75 There is ample evidence that evaluating bruising patterns in abused and nonabused children helps to identify specific ages, locations, and patterns of bruising that are highly correlated with child abuse. [76][77][78][79][80][81] In children with bruising related to normal activity, the prevalence and mean number of bruises increases with age, and the majority of preschool-aged and schoolchildren have accidental bruises. 82 The commonest sites of bruising in nonabused, ambulatory children are to the knees and shins, and the vast majority of normal bruises are over bony prominences, including the forehead.…”
Section: Skin Injuriesmentioning
confidence: 99%
“…78 All parts of the body are vulnerable to bruising from abuse, and bruises to the torso, ears, or neck in children #4 years of age are predictive of abuse. 76 The mnemonic "TEN 4" is an easy way to identify bruises that are of concern for abuse:…”
Section: Skin Injuriesmentioning
confidence: 99%
“…103,104 Bruising in a child who is not yet cruising or bruising in unusual locations, such as the ears, neck, or trunk should raise suspicion for child abuse. 105,106 The child should be examined for other injuries caused by child abuse, in addition to signs of other medical conditions associated with bone fragility. Blue sclerae are seen in certain types of OI.…”
Section: Physical Examinationmentioning
confidence: 99%
“…14,15 Several studies have identified characteristics of bruises associated with abusive versus accidental injury, but clear guidelines for clinicians regarding when to perform an initial SS for abuse in young children with bruising have not been developed. 1,16 Accordingly, the goal of this study was to develop guidelines for performing initial SS in children ,2 years old presenting with bruising. This set of guidelines focuses on children presenting for care in a hospitalbased setting, primarily the emergency department or the inpatient unit, and may not be applicable to children presenting in the primary care setting.…”
Section: What This Study Addsmentioning
confidence: 99%